The Shaping of New Ethnic Clusters in Kalmykia, 1957–1991 - Sergey S. Belousov (Oriental Studies)
Introduction. The article discusses the shaping of largest ethnic clusters (besides those of Kalmyks and Russians proper) across the Kalmyk ASSR in 1957–1991. The process is of certain scientific and practical interest, since it may extend our knowledge of how ethnic structures in Russia would take shape, including in the particular region of Kalmykia. Goals. The article aims at outlining the specified process in the territory of the Kalmyk ASSR at the final stage of the Soviet era. The study employs the historical/comparative and historical/genetic methods to examine materials from the National Archive of Kalmykia, published documents and statistical tables, republican newspaper articles. Results. The work investigates some circumstances behind the emergence of new ethnic clusters, shows their population dynamics, types and forms of resettlement, analyzes official policies and interethnic relations between locals and migrants. The present-day ethnic structure of Kalmykia started taking shape after the Kalmyk people’s autonomy was restored in 1957. The Government invested considerable funds to reconstruct and develop the Kalmyk ASSR but the available labor resources of Kalmyk homecomers and Russian natives were insufficient. So, the authorities were forced to recruit laborers in other regions. Stable new ethnic communities emerged in rural areas, the majority of the migrants having arrived from neighboring North Caucasian republics then characterized by intense population growth and excess labor resources. Shortly before the collapse of the Soviet Union, urgently evacuated Meskhetian Turks and Kurds were also resettled to the republic. Conclusions. The emergence of new ethnic clusters in the Kalmyk ASSR was facilitated by the Government’s large investments that resulted in increased jobs unable to be filled by homecomers and locals. There were no special ethnic resettlement projects but the granted employment opportunities in the reestablished republic were attractive enough, which led to a migration surge and the shaping of new ethnic communities.